Triplet (FOLFOXIRI) versus doublet (FOLFOX or FOLFIRI) backbone chemotherapy as first-line treatment of metastatic colorectal cancer: A systematic review and meta-analysis. (October 2017) - Marques, Rui Pedro; Duarte, Gonçalo S.; Sterrantino, Carmelo; Pais, Helena Luna; Quintela, António; Martins, Ana Paula; Costa, João
Highlights: Uncertainty exists regarding initial chemotherapy for metastatic colorectal cancer. Recent trials with FOLFOXIRI suggest it could be an important alternative to doublets. A systematic review and meta-analysis of RCTs was used to aggregate existing evidence. FOLFOXIRI in mCRC was associated with higher efficacy than standard doublet regimens. Increased risk of grade ≥3 AEs was considered, in some contexts, lower than expected. Abstract: Uncertainty exists regarding the comparative effectiveness of triplet chemotherapy (FOLFOXIRI) as backbone first-line chemotherapy for metastatic colorectal cancer (mCRC). We conducted a systematic review and meta-analysis of randomized-controlled trials (RCTs) comparing triplet versus doublet chemotherapy (FOLFOX or FOLFIRI) as first-line therapy in mCRC. Methods and reporting followed PRISMA and SAMPL guidelines. Eight RCTs were included, comprising 1732 patients. In pooled analysis, FOLFOXIRI was associated with improvements in efficacy outcomes, notably with a 25% survival increase (95%CI: 10–37%). FOLFOXIRI was also associated with increased toxicity, with a non-significant 25% increase in the risk of patients experiencing grade ≥3 adverse events (95% CI: −3 to 61%) and with a 1.83 (95% CI: 1.62–2.07) increase in the rate ratio of grade ≥3 adverse events. Moderate quality evidence suggests that first-line FOLFOXIRI provides clinically meaningful efficacy benefits in this setting, at the expense of increased toxicity. Further research is warranted to better characterize safety and to evaluate the most beneficial combination with targeted agents.